1980
DOI: 10.1038/288665a0
|View full text |Cite
|
Sign up to set email alerts
|

Moloney murine sarcoma proviral DNA is a transcriptional unit

Abstract: A portion of Moloney murine sarcoma virus DNA which is repeated at both ends of the provirus has been sequences. The nucleotide sequence, together with hybridization data obtained with in vitro pulse-labelled nascent viral RNA, indicate that initiation and termination of RNA synthesis occur within that region of the proviral DNA. A model for transcriptional readthrough of termination signals during RNA synthesis in this system is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 45 publications
1
46
0
Order By: Relevance
“…The viral TATA box and following sequences were not replaced in these vectors, since the terminal bases of U3 are necessary for recognition of the polyadenylation signal in the 3Ј LTR. 24 Virus harvested from bulk populations of stable TE-FLY-A8 transfectants was used to infect PAE and TE671 target cells. Endogenous expression in PAE cells was confirmed by RT-PCR using primers specific for porcine ppET1, whereas no endogenous expression was detected in TE671 cells (data not shown) that were subsequently used as a negative control.…”
Section: Generation Of Retroviral Vectors With Hybrid Ltr By Replacemmentioning
confidence: 99%
“…The viral TATA box and following sequences were not replaced in these vectors, since the terminal bases of U3 are necessary for recognition of the polyadenylation signal in the 3Ј LTR. 24 Virus harvested from bulk populations of stable TE-FLY-A8 transfectants was used to infect PAE and TE671 target cells. Endogenous expression in PAE cells was confirmed by RT-PCR using primers specific for porcine ppET1, whereas no endogenous expression was detected in TE671 cells (data not shown) that were subsequently used as a negative control.…”
Section: Generation Of Retroviral Vectors With Hybrid Ltr By Replacemmentioning
confidence: 99%
“…lA), leads to the functional difference between the retroviral 5' and 3' poly(A) sites (Benz et al 1980;Dougherty and Temin 1987). However, we have shown that this hypothesis is unlikely (Iwasaki and Temin 1990).…”
mentioning
confidence: 97%
“…3,1983 on May 12, 2018 by guest http://mcb.asm.org/ Downloaded from was cleaved with PstI, which excised the major central region (approximately 3.95 kb) of the Mo-MSV genome. This left intact the 5' and 3' LTR sequences and short lengths of Mo-MSV sequences immediately adjacent to the LTRs, whose significance will be discussed later.…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence that the origin of certain rapidly transforming murine retroviruses, for example, Moloney murine sarcoma virus (Mo-MSV), occurs by the recombination of Moloney murine leukemia virus (MoMuLV) with a cellular gene or oncogene (c-mos) normally present in the mouse genome (17,27). The gene now carried by the virus (designated vmos) becomes integrated, apparently randomly, into the genome of cells infected with Mo-MSV, where it is expressed at a high level and thus leads to cell transformation (3,12). Except for Rous sarcoma virus, the rapidly transforming retroviruses are replication defective, but they can be packaged in virion coats in the presence of a suitable helper retrovirus (43).…”
mentioning
confidence: 99%